2017
DOI: 10.1016/j.heares.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stimulus level on the temporal response properties of the auditory nerve in cochlear implants

Abstract: Electrically evoked compound action potentials (ECAPs) have been used to examine temporal response patterns of the auditory nerve in cochlear implant (CI) recipients. ECAP responses to individual pulses in a pulse train vary across stimulation rates for individual CI users. For very slow rates, auditory neurons have ample time to discharge, recover, and respond to each pulse in the train. As the pulse rate increases, an alternating ECAP-amplitude pattern occurs. As the stimulation rate increases further, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…In addition to acoustic stimulation, AN fibers adapt to continuous electrical stimulation (e.g., Wilson et al 1997;Haenggeli et al 1998;Matsuoka et al 2000aMatsuoka et al , 2000bLitvak et al 2001;Hay-McCutcheon et al 2005;Zhang et al 2007;Miller et al 2008;Heffer et al 2010;Hughes et al 2012Hughes et al , 2014He et al 2016;Hughes & Laurello 2017). Results of single-unit studies using animal models demonstrated that the discharge rate of electrically stimulated AN fibers to sustained pulse-train stimulation showed a rapid decline followed by a gradual decrease over the course of up to 200 ms (van den Honert & Stypulkowski 1987;Javel et al 1987;Litvak et al 2001;Zhang et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to acoustic stimulation, AN fibers adapt to continuous electrical stimulation (e.g., Wilson et al 1997;Haenggeli et al 1998;Matsuoka et al 2000aMatsuoka et al , 2000bLitvak et al 2001;Hay-McCutcheon et al 2005;Zhang et al 2007;Miller et al 2008;Heffer et al 2010;Hughes et al 2012Hughes et al , 2014He et al 2016;Hughes & Laurello 2017). Results of single-unit studies using animal models demonstrated that the discharge rate of electrically stimulated AN fibers to sustained pulse-train stimulation showed a rapid decline followed by a gradual decrease over the course of up to 200 ms (van den Honert & Stypulkowski 1987;Javel et al 1987;Litvak et al 2001;Zhang et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with results reported in animal models, data recorded in human CI users demonstrate a greater degree of alternation across a wider range of stimulation levels and pulse rates (Wilson et al 1994;Finley et al 1997;Matsuoka et al 2000a). This alternating response pattern disappears at higher pulse rates due to combined effects of refractory recovery, adaptation, and increased temporal jitter (Wilson et al 1997;Hay-McCutcheon et al 2005;Mino and Rubinstein 2006;Miller et al 2008;Hughes et al 2012Hughes et al , 2014McKay et al 2013;He et al 2016;Hughes & Laurello 2017). The rate at which the alternating pattern is no longer evident is defined as the stochastic rate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Postoperative NRT testing may be indicated to assess neural recovery functions to gain information about beneficial stimulation rates. From their studies on the temporal characteristics of auditory nerve stimulation via CIs, [16] suggest that the programmed stimulation rate relates to the refractory period of the nerve. CI user performance may be addressed, in some cases, by reducing the stimulation rate.…”
Section: Optimizing Maps and Initial Evaluations: 1-month Follow-upmentioning
confidence: 99%